A Clinicopathological Analysis of Melanocytic Nevi: A Retrospective Series - Liu, Panpan; Su, Juan; Zheng, Xuanwei; Chen, Mingliang; Chen, Xiang; Li, Jie; Peng, Cong; Kuang, Yehong; Zhu, Wu (Frontiers in Medicine, 2021)
Purpose Melanocytic nevi are common cutaneous lesions. This study aimed to demonstrate the concordance and discordance between clinical and histopathological diagnoses of melanocytic nevi and the importance of histological evaluation in differentiating malignant lesions from diseases with similar clinical manifestations. Patients and Methods We studied 4561 consecutive patients with a clinical diagnosis of melanocytic nevi from 2014 to 2019. We compared the clinical diagnosis with the histopathological diagnosis to establish a histopathological concordance rate and then investigated the effects of clinical characteristics and the reasons for removal on misclassification. Results Among 4561 patients who were clinically diagnosed with melanocytic nevi, the overall histopathological concordance rate was 82.11% (3745 of 4561 patients), while the histopathological discordance rate was 17.89% (816 of 4561 patients). The histopathological concordance included 90.25% common acquired melanocytic nevi (3380 of 3745 patients) and 9.75% other benign melanocytic neoplasms (365 of 3745 patients). The most common diagnostic change was to seborrheic keratosis (n=470, 10.30%), followed by basal cell carcinoma (n=64, 1.40%), vascular tumor (n=53, 1.16%), fibroma (n=43, 0.94%), epidermoid cyst (n=34, 0.75%), wart (n=30, 0.66%), melanoma (n=24, 0.53%), Bowen’s disease (n=16, 0.35%), squamous cell carcinoma (n=4, 0.09%), keratoacanthoma (n=2, 0.04%), and other neoplasms (n=76, 1.67%). Male sex, old age, location of the lesion, and the reasons for removal have a potential effect on misclassification. The percentages of misclassified lesions on the trunk and limbs and perineum and buttocks were higher than those in lesions without a change in diagnosis. Importantly, locations of the lesions on the head and neck were significantly related to a change in diagnosis to non-melanoma skin cancer, while locations on the hands and feet were significantly related to a change in diagnosis to melanoma. In addition to atypical clinical features, removal due to lesion changes or repeated stimulation was significantly associated with a change in the diagnosis to melanoma. Conclusions Our study emphasizes the clinical differential diagnosis of melanocytic nevi, especially the possibility of malignant tumors. The occurrence of clinical features associated with clinicopathological discordance should raise the clinical suspect and be carefully differentiated from malignant tumors.